3D Thermally Cross‐Linked Graphene Aerogel–Enhanced Silicone Rubber Elastomer as Thermal Interface Material. Issue 12 (3rd May 2019) - Zhang, Wenya; Kong, Qing‐Qiang; Tao, Zechao; Wei, Jiacheng; Xie, Lijing; Cui, Xiaoyu; Chen, Cheng‐Meng
Abstract: Efficient heat dissipation is becoming a key limiting factor for the next‐generation smart electronic devices with ever‐increasing power density. The thermal interface materials (TIMs), with high out‐of‐plane thermal conductivity (TC) and excellent mechanical properties, are thus highly desired. In the present work, an elastomer‐type TIM is fabricated with silicone rubber (SR) as the matrix, and 3D interconnected graphene aerogel (gGA) as the nano‐filler. The lattice defects of graphene are remarkably repaired by graphitization at over 2800 °C, probably with chemical covalent bonding between the graphene sheets, so as to decrease the interfacial phonon scattering. What is more, the results of X‐ray diffraction and Raman spectroscopy confirm the thorough reduction and defects repair of 3D continuous graphene network, which can accelerate the heat dissipation. By vacuum/pressure alternate assisted impregnation, the as‐obtained gGA/SR composites show a consolidate structure with superior mechanical flexibility, which is desirable for TIMs. The TC reaches up to 1.26 W m −1 K −1 at a very low gGA loading of 0.50 wt%, which is 448% higher than that of pure SR (0.23 W m −1 K −1 ). This indicates that the 3D crossed‐linked graphene aerogel is an effective scaffold for enhancing the heat dissipation performance of advanced thermal management materials. Abstract : Thermal interface material is a key part of the thermal management system of electronic devices. Inspired by welding, a high thermal conductive 3D continuous network obtained by graphitizing at 2800 °C is used as a reinforcement of graphene aerogel/silicon rubber composite. The thermal conductivity enhancement by per weight graphene is as high as 896%.